Drug Induced Syndromes: An Overview - BJ, Mahendra Kumar; M, Soumya; K, Jyothi; B. D, Jagadish (Indian Journal of Pharmacy Practice)
Many drugs have come into the market in recent years and its usage is increased for multiple disorders which in turn leads to poly pharmacy and increased drug related problems. One such drug related problem is Drug-induced syndrome. These syndromes are one of the major problems in the health care sector. Drug related problems are found to be a reason for hospital admission and also for an increased patients stay in the hospital. The syndromes can be associated with any pathological conditions or may be drug related. This overview article provides the information regarding the different drug induced syndromes with its causative agents, clinical manifestation and therapy.
Keywords: Drug induced syndrome; drug related problem